2012
DOI: 10.1016/j.jiph.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in behavioral reactions to H1N1 during a later stage of the epidemic

Abstract: Previous studies regarding individuals' behavioral reactions to the H1N1 epidemic have been conducted nearly exclusively on the pre-pandemic phase of the epidemic or when the vaccine was not available. The prevalence and correlates of behavioral reactions to the H1N1 epidemic in Turkey were investigated by surveying 1045 respondents. The results indicate that behavioral responses can be divided into three classifications: recommended protective behaviors, avoidance behaviors, and ineffective behaviors. The fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 19 publications
(44 reference statements)
3
61
0
Order By: Relevance
“…The I-Change model has exibility to support wider factors including predisposing factors, which in this study, allowed inclusion of habit and time factors from Aunger's classi cation for handwashing [18], and trust which was present in the WHO survey and appears in other studies [27,30]. Both habit and time factor statement responses showed variability in this sample although were skewed towards agreement.…”
Section: Investigation Of Knowledge/socio-cognitive Perception Towardmentioning
confidence: 82%
See 1 more Smart Citation
“…The I-Change model has exibility to support wider factors including predisposing factors, which in this study, allowed inclusion of habit and time factors from Aunger's classi cation for handwashing [18], and trust which was present in the WHO survey and appears in other studies [27,30]. Both habit and time factor statement responses showed variability in this sample although were skewed towards agreement.…”
Section: Investigation Of Knowledge/socio-cognitive Perception Towardmentioning
confidence: 82%
“…The Integrated-Change (I-Change) model integrates a range of socio-cognitive theories to explain behavioural changes by looking at pre-motivational factors such as knowledge and risk perception, as well as motivational factors such as attitude, social norms and self-e cacy [29]. It also includes predisposing factors which can represent a wide range of behavioural, psychological, biological and environmental factors, and hence can provided a comprehensive framework for investigating a wide variety of potential determinants, including habit, time factors [18] and trust [30]. Therefore, the current study used I-Change as a theoretical framework.…”
Section: Introductionmentioning
confidence: 99%
“…Compliance with social distancing and hygiene measures (i.e. hand washing), was found to be greater in those of older age, in parents of children aged 18 or less, in women compared to men, and in people with higher SEP [18,35,38,39,41,42,45-48]. …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, openness predicts healthy outcomes. In this regard, a study (Gaygısız, Gaygisiz, Ozkan, & Lajunen, 2012) on the behavioral reactions to the A/H1N1 virus during the later stage of the epidemic showed that personality factors moderately influenced the behavioral responses. The belief of the individuals in the effectiveness of their behavior was the primary factor that influenced the behavioral responses.…”
Section: Psychological Variables and Infectious Diseasesmentioning
confidence: 99%